Quantitative physiology and biomass composition of Cyberlindnera jadinii in ethanol-grown cultures - Marcel A. Vieira-Lara; Marieke Warmerdam; Erik A. F. de Hulster; Marcel van den Broek; Jean-Marc Daran; Jack T. Pronk (Biotechnology for Biofuels and Bioproducts)
Abstract Background Elimination of greenhouse gas emissions in industrial biotechnology requires replacement of carbohydrates by alternative carbon substrates, produced from CO2 and waste streams. Ethanol is already industrially produced from agricultural residues and waste gas and is miscible with water, self-sterilizing and energy-dense. The yeast C. jadinii can grow on ethanol and has a history in the production of single-cell protein (SCP) for feed and food applications. To address a knowledge gap in quantitative physiology of C. jadinii during growth on ethanol, this study investigates growth kinetics, growth energetics, nutritional requirements, and biomass composition of C. jadinii strains in batch, chemostat and fed-batch cultures. Results In aerobic, ethanol-limited chemostat cultures, C. jadinii CBS 621 exhibited a maximum biomass yield on ethanol ( $$Y_{X/S}^{\max}$$ Y X / S max ) of 0.83 g biomass (gethanol)−1 and an estimated maintenance requirement for ATP (m ATP) of 2.7 mmolATP (gbiomass)−1 h−1. Even at specific growth rates below 0.05 h−1, a stable protein content of approximately 0.54 gprotein (gbiomass)−1 was observed. At low specific growth rates, up to 17% of the proteome consisted of alcohol dehydrogenase proteins, followed by aldehyde dehydrogenases and acetyl-CoA synthetase. Of 13 C. jadinii strains evaluated, 11 displayed fast growth on ethanol (μ max > 0.4 h−1) in mineral medium without vitamins, and CBS 621 was found to be a thiamine auxotroph. The prototrophic strain C. jadinii CBS 5947 was grown on an inorganic salts medium in fed-batch cultures (10-L scale) fed with pure ethanol. Biomass concentrations in these cultures increased up to 100 gbiomass (kgbroth)−1, with a biomass yield of 0.65 gbiomass (gethanol)−1. Model-based simulation, based on quantitative parameters determined in chemostat cultures, adequately predicted biomass production. A different protein content of chemostat- and fed-batch-grown biomass (54 and 42%, respectively) may reflect the more dynamic conditions in fed-batch cultures. Conclusions Analysis of ethanol-grown batch, chemostat and fed-batch cultures provided a quantitative physiology baseline for fundamental and applied research on C. jadinii. Its high maximum growth rate, high energetic efficiency of ethanol dissimilation, simple nutritional requirements and high protein content, make C. jadinii a highly interesting platform for production of SCP and other products from ethanol.